Uji Tingkat Keasaman dan Sifat Fisik Yoghurt dengan Penambahan Ekstrak Daun Pegagan (Centella asiatica) dan Bunga Rosella (Hibiscus sabdariffa) - Muhammad Fadillah; Miladya Syamsu; Siska Aprilia Kaulika (Risenologi, 2022)
Yogurt is one type of fermented dairy that has a fresh sour taste. This drink contains probiotic bacteria that can improve digestive health. The nutritional content of yoghurt can be enriched by adding other herbal food ingredients, for example, cica leaf extract and rosella flower. This study tested the effect of the addition of pegagan leaf extract and rosella flowers on the acidity of yogurt. Experimental research methods using Complete Random Design (CRD) with two combinations of the same treatment, the ratio of gotu kola leaf extract and rosella flower 1:1 and 2:1. There are 2 tests, which are the pH test with a pH meter and the titrated total acid test (TAT). The results of the two tests found that there was no significant change in pH or total titrated acid.